COMMENTARY: THE PROMISE OF DIGITAL SCHOLARSHIP IN SLA RESEARCH AND LANGUAGE PEDAGOGY - Sally Sieloff Magnan (Language Learning and Technology)
Although digital scholarship is now well established in academia, there is no consensus about how it should be evaluated for tenure and promotion. Is digital publication acceptable as a way to disseminate research? Is the digital medium appropriate for conducting research? To what degree does creating digital materials--from research instruments to pedagogical materials--advance knowledge and thereby constitute scholarship? Recent calls for open access to scholarship (i.e., free publication and dissemination) through digital media (see Chanier, 2007) are stimulating a debate that hinges on just such questions. In that debate, departments holding traditional views hesitate to recognize digital media as scholarship while others hold that digital media promises to enrich scholarly exchanges. In 2001, the Modern Language Association entered the controversy by offering its Guidelines for Evaluating Work with Digital Media in the Modern Languages (MLA, 2001). These Guidelines are the work of the Committee on Information Technology, formerly the MLA Committee on Computers and Emerging Technologies in Teaching and Research. They aim to help departments achieve an informed perspective on this new scholarly medium. In this commentary, I offer additional thoughts to the debate by considering (a) how digital media necessitates a redefinition of scholarship in second language acquisition (SLA) research and language pedagogy, (b) what criteria might be used in evaluating digital scholarship, and (c) how digital media enhances and accelerates SLA scholarship beyond the possibilities of print publication.